2020
DOI: 10.1177/0300060520936177
|View full text |Cite
|
Sign up to set email alerts
|

Dl-3-n-butylphthalide regulates cholinergic dysfunction in chronic cerebral hypoperfusion rats

Abstract: Objectives To investigate whether dl-3-n-butylphthalide (NBP) affects cholinergic system function and ameliorates cognitive decline in a rat model of vascular dementia (VaD). Methods The VaD rat model was established by bilateral common carotid artery ligation (two-vessel occlusion, 2VO). Rats were divided into five groups: control, sham, 2VO, 2VO+NBP (80 mg/kg; intragastric), and 2VO+donepezil (1 mg/kg; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Acetylcholine plays an important part in regulating biological rhythms (e.g., wakefulness, sleep), stress response, inflammatory response, and vascular tone (Jin et al, 2015). In line with earlier findings (Sun et al, 2020), in this study, CH increased the AChE activity that might adversely affect the acetylcholine levels in the brain. Following the energy depletion and ionic imbalance, accumulation of glutamate in synapse depolarizes the postsynaptic membrane, triggers Ca 2+ influx and nitric oxide release that establishes a vicious cycle of Ca 2+dependent catabolic (proteolytic) mechanisms (Belov Kirdajova et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Acetylcholine plays an important part in regulating biological rhythms (e.g., wakefulness, sleep), stress response, inflammatory response, and vascular tone (Jin et al, 2015). In line with earlier findings (Sun et al, 2020), in this study, CH increased the AChE activity that might adversely affect the acetylcholine levels in the brain. Following the energy depletion and ionic imbalance, accumulation of glutamate in synapse depolarizes the postsynaptic membrane, triggers Ca 2+ influx and nitric oxide release that establishes a vicious cycle of Ca 2+dependent catabolic (proteolytic) mechanisms (Belov Kirdajova et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…DL-3-n-butylphthalide (NBP) is a new drug developed independently in China that acts on multiple pathological links of acute ischemic stroke ( Wang et al, 2018 ). In addition to promoting the recovery of cognitive function after stroke, recent clinical studies have demonstrated that NBP can improve the oxidative stress response of the nervous system ( Lv et al, 2018 ), inhibit neuronal apoptosis and autophagy ( Xu J et al, 2017 ), regulate central cholinergic function ( Zhao et al, 2014 ; Sun et al, 2020 ) and promote neuroplasticity ( Yang et al, 2015 ). A randomized controlled study involving 281 patients with subcortical nondementia VCI also showed that 6 months of NBP treatment effectively improved the cognitive and overall function of patients ( Jia et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effect of dl-3-n-butylphthalide (NBP) on hippocampal expression levels of ChAT, acetylcholinesterase (AChE), vesicular acetylcholine transporter (VAChT), and the BDNF was examined. A rat model of vascular dementia established by bilateral common carotid artery ligation exhibited decreased spatial learning and memory evaluated with a Morris water maze test, although administration of NBP reversed the decreased learning and memory function [ 66 ]. NBP treatment also increased ChAT, AChE, VAChT, and BDNF expressions, suggesting that central cholinergic dysfunction is involved in vascular dementia pathogenesis and NBP is effective to protect the cholinergic system via activating the BDNF signaling [ 66 ].…”
Section: Bdnf Signaling In Admentioning
confidence: 99%
“…A rat model of vascular dementia established by bilateral common carotid artery ligation exhibited decreased spatial learning and memory evaluated with a Morris water maze test, although administration of NBP reversed the decreased learning and memory function [ 66 ]. NBP treatment also increased ChAT, AChE, VAChT, and BDNF expressions, suggesting that central cholinergic dysfunction is involved in vascular dementia pathogenesis and NBP is effective to protect the cholinergic system via activating the BDNF signaling [ 66 ]. Interestingly, the influence of focused ultrasound (FUS)-mediated blood–brain barrier opening in the cholinergic degeneration rat model was reported [ 67 ].…”
Section: Bdnf Signaling In Admentioning
confidence: 99%